2012
DOI: 10.1186/1758-2555-4-48
|View full text |Cite
|
Sign up to set email alerts
|

Management of degenerative rotator cuff tears: a review and treatment strategy

Abstract: The aim of this review was to present an over view of degenerative rotator cuff tears and a suggested management protocol based upon current evidence. Degenerative rotator cuff tears are common and are a major cause of pain and shoulder dysfunction. The management of these tears is controversial, as to whether they should be managed non-operatively or operatively. In addition when operative intervention is undertaken, there is question as to what technique of repair should be used. This review describes the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 47 publications
(46 reference statements)
0
41
0
5
Order By: Relevance
“…30 As individuals age, they continue to acquire degenerative changes over time, leading to distortion of the normal shoulder anatomy, as demonstrated by Clement et al in a 2012 review stating that up to 54% of people older than 65 years have partial or complete tears of the RTC seen on magnetic resonance imaging. 9 Although no comparable studies have been performed looking specifically at LHB disease, it is likely that an analogous trend exists. More important, our study demonstrates a statistically significant difference in the performance of arthroscopic vs. open tenodesis in 1-on-1 comparisons of different primary diagnoses (Table VII).…”
Section: Arthroscopic Tenodesismentioning
confidence: 94%
“…30 As individuals age, they continue to acquire degenerative changes over time, leading to distortion of the normal shoulder anatomy, as demonstrated by Clement et al in a 2012 review stating that up to 54% of people older than 65 years have partial or complete tears of the RTC seen on magnetic resonance imaging. 9 Although no comparable studies have been performed looking specifically at LHB disease, it is likely that an analogous trend exists. More important, our study demonstrates a statistically significant difference in the performance of arthroscopic vs. open tenodesis in 1-on-1 comparisons of different primary diagnoses (Table VII).…”
Section: Arthroscopic Tenodesismentioning
confidence: 94%
“…In this retrospective study, which included only patients with full-thickness tears (44 patients); an acute RCT was defined as when the clinical history revealed a distinct injury within 6 months of the time of the operation in a previously asymptomatic shoulder. It was found that SBEs were significantly more common among those patients with acute RCT tears than those with chronic tears (6). In another study, it was found that an SBE was more commonly associated with current or previous symptomatic tears compared to asymptomatic tears (8).…”
Section: Discussionmentioning
confidence: 85%
“…An RCT can be associated with limited shoulder movement in addition to pain, and the treatment can include several strategies, such as non-steroidal anti-inflammatory drugs, local corticosteroid injections, local hyaluronic acid injections, and/or surgery (6). The chronicity of shoulder pain is one of the most important factors in the success of any treatment (1).…”
Section: Introductionmentioning
confidence: 99%
“…They can also include patient educational strategies in order to avoid progression or recurrence of the injury [101112]. Conventional rehabilitation programs have proven effective in a high proportion of patients with RC tears [1314].…”
Section: Introductionmentioning
confidence: 99%